Child Perspective Of The World Reflected In Emma Donoghue's Room (2010) Novel: A Sociological Approach - Nurhayati, Eka, Dr. M. Thoyibi, M.S (2017)
This research was to analyze child perspective in the novel of Emma Donoghue's Room that published in 2010 by using sociological approach. The researcher used qualitative research to describe child's perspective through child perspective. Primary data and secondary data are two types of data in this study. Primary data consisting of words, sentences, and dialog related to the issue and the others references as the secondary data. The result showed that Jack as 5-year-old child showed the indicators such as animistic, egocentrism, non-logical thinking, magical thinking, and imaginative that occurs in early childhood. The other result related sociology of literature that showed that literary as reflection social situation of the author influenced the author of novel to write this novel used child perspective as the reflection of the novel's author and reflection of being a mother who tries to understand children's world. In conclusion, child perspective in this research can be known through adult view the way of thinking in children that refers to animistic and full of imagination life that usually occurs in early childhood.